Pengaruh strategi Penetapan harga, Kualitas Layanan, Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Pada Umkm Kacang Tanah Di Wilayah Wonomerto Probolinggo (Studi Pada UMKM Kacang Tanah Di Desa Pohsangit Lor) - Idrus, M; Djaelani, Abdul Kodir; Rahmawati, Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the effect of pricing strategy, service quality, and customer satisfaction on customer loyalty in peanut UMKM in Pohsangit Lor Village, Wonomerto District, Probolinggo Regency. In an era of increasingly tight business competition, understanding the factors that influence customer loyalty is crucial for UMKM in order to survive and grow.The research method used is a quantitative approach with data collection techniques through questionnaires distributed to peanut UMKM customers in the area. The data obtained were analyzed using multiple linear regression methods to determine the effect of each variable on customer loyalty.The results of the study indicate that pricing strategy has a significant effect on customer loyalty, indicating that competitive prices can increase customer retention. In addition, service quality also contributes positively to building customer loyalty, where good service increases customer satisfaction and attachment to the product. Customer satisfaction is proven to be a mediating variable that strengthens the relationship between pricing strategy and service quality on customer loyalty.Thus, peanut MSMEs in Pohsangit Lor Village are advised to continue to improve service quality and implement pricing strategies that are in accordance with customer preferences in order to increase customer loyalty. Keywords: The Influence of Pricing Strategy, Service Quality, and Customer Satisfaction on Customer Loyalty